Negotiating disease : power and cancer care, 1900-1950 - Clow, Barbara Natalie, 1959- (Montreal ; Ithaca : McGill-Queen's University Press, 2001)
"Criticism of conventional medicine is often regarded as a product of the 1960s. Before then, "scientific medicine" enjoyed uncontested cultural prestige, with kindly but strict doctors wielding unquestioned authority over grateful patients while "quacks" flogged dubious remedies to the poor and credulous - or so go popular perceptions and, for the most part, received scholarly wisdom. But the very nature of cancer - mysterious, capricious, and deadly - challenged medical authority in the past as much as it does today, and in Negotiating Disease Barbara Clow lays to rest old assumptions about the monopoly of health care by doctors in the first half of the twentieth century."--Jacket
Introduction: Framing a Response to Disease -- 1. Health Begins at Home: Lay Perceptions of Illness, Disease, and Doctors -- 2. The Problem of Cancer: Doctors, Scientists, and the Dread Disease -- 3. The Contours of Legitimate Medicine: Doctors, Alternative Practitioners, and Cancer -- 4. Cancer Patients Take Care: Sufferers, Healers, and Illness Experiences -- 5. Negotiating a Response to Disease: Politics and Cancer -- Conclusion: Authority, Legitimacy, and the Problem of Cancer.
Includes bibliographical references (pages 209-232) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Cancer -- Alternative treatment -- Canada; Cancer -- Government policy -- Canada; Medical personnel and patient -- Canada -- History; Cancer -- Treatment -- Ontario -- History -- 20th century; Medical Oncology -- history; History, 20th Century; Neoplasms -- history; Canada; Cancer -- Traitement -- Ontario -- Histoire -- 20e siècle.; Cancer -- Médecines parallèles -- Canada; Cancer -- Politique gouvernementale -- Canada; Relations personnel médical-patient -- Canada -- Histoire; Médecine -- Histoire -- 20e siècle.; HEALTH & FITNESS -- Diseases -- Cancer; MEDICAL -- Oncology; Cancer -- Treatment; Cancer -- Alternative treatment; Cancer -- Government policy; Medical personnel and patient; Ontario; Canada; Cancer -- Traitement -- Ontario -- Histoire -- 20e siècle.; 1900-1999; Electronic books; History